2017
DOI: 10.1038/aps.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibitor 3-methyladenine alleviates overload-exercise-induced cardiac injury in rats

Abstract: Overload-exercise (OE) causes myocardial injury through inducing autophagy and apoptosis. In this study we examined whether an autophagy inhibitor 3-methyladenine (3-MA) could alleviate OE-induced cardiac injury. Rats were injected with 3-MA (15 mg/kg, iv) or saline before subjected to various intensities of OE, including no swim (control), 2 h swim (mild-intensity exercise, MIE), 2 h swim with 2.5% body weight overload (moderate OE; MOE), 5% overload (intensive OE; IOE) or 2.5% overload until exhausted (exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Speci cally, the DS-BC and CR-BC cells were subjected to high-dose Dox stimulation, and we found that Dox stimulation speci cally increased LC3B-II/I ratio, decreased p62 expression levels and facilitated autophagosomes formation in DR-BC cells, instead of DS-BC cells, suggesting that autophagy was activated in DR-BC cells under Dox pressure. Given the fact that autophagy protected cells from death [13,14], we next explored whether autophagy was pivotal for regulating Dox-resistance in BC cells by utilizing its inhibitor 3-methyladenine (3-MA) [23]. As expected, the results showed that 3-MA inhibited autophagy in DR-BC cells treated with Dox.…”
Section: Discussionmentioning
confidence: 77%
“…Speci cally, the DS-BC and CR-BC cells were subjected to high-dose Dox stimulation, and we found that Dox stimulation speci cally increased LC3B-II/I ratio, decreased p62 expression levels and facilitated autophagosomes formation in DR-BC cells, instead of DS-BC cells, suggesting that autophagy was activated in DR-BC cells under Dox pressure. Given the fact that autophagy protected cells from death [13,14], we next explored whether autophagy was pivotal for regulating Dox-resistance in BC cells by utilizing its inhibitor 3-methyladenine (3-MA) [23]. As expected, the results showed that 3-MA inhibited autophagy in DR-BC cells treated with Dox.…”
Section: Discussionmentioning
confidence: 77%
“…Speci cally, the DS-BC and CR-BC cells were subjected to high-dose Dox stimulation, and we found that Dox stimulation speci cally increased LC3B-II/I ratio, decreased p62 expression levels and facilitated autophagosomes formation in DR-BC cells, instead of DS-BC cells, suggesting that autophagy was activated in DR-BC cells under Dox pressure. Given the fact that autophagy protected cells from death [13,14], we next explored whether autophagy was pivotal for regulating Dox-resistance in BC cells by utilizing its inhibitor 3methyladenine (3-MA) [23]. As expected, the results showed that 3-MA inhibited autophagy in DR-BC cells treated with Dox.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, the detailed mechanisms are still not fully understood. To solve this issue, the inhibitor for autophagy, 3-methyladenine (3-MA) [23], was used in this study, and we validated that 3-MA aggravated the inhibiting effects of Dox on cell proliferation in Dox-resistant BC (DR-BC) cells, which rendered the possibility that autophagy might play a protective role to enhance Dox-resistance under high-dose Dox stimulation in BC cells. AMP-activated protein kinase (AMPK)-Unc-51-like kinase 1 (ULK1) signaling cascade was crucial for autophagy initiation [24][25][26], and activation of AMPK-ULK1 pathway triggered protective autophagy to promote cell survival under environmental stress, such as oxidative stress [27] and cigarette smoke exposure [28].…”
Section: Ed Thatmentioning
confidence: 87%
“…Li et al [ 35 ] verified that an acute exhaustive exercise session suppressed autophagy, which was linked to ischemia-hypoxia injury in rat myocardium. In contrast, exhaustive overload-exercise-induced autophagy was related to disrupted cardiomyocytes [ 36 ]. According to Sciarretta and coworkers [ 37 ], the functional implications of the induction or suppression of the autophagy pathway in the heart under different experimental conditions must be further investigated.…”
Section: Discussionmentioning
confidence: 99%